Long Term Olfactory Outcomes Following Frontal Sinus Surgery in Chronic Rhinosinusitis. (22nd March 2021) - Ninan, Sen; Goldrich, David Y.; Liu, Katherine; Kidwai, Sarah; McKee, Sean; Williams, Lauren; Del Signore, Anthony; Govindaraj, Satish; Iloreta, Alfred M.
Abstract : Objectives/Hypothesis: No studies have evaluated the impact of the types of frontal sinus surgery (FSS) on objective olfaction scores. This study evaluated olfactory function and quality of life (QOL) in chronic rhinosinusitis (CRS) patients before and after total ethmoidectomy with frontal sinusotomy (FS). Study Design: Prospective cohort study. Methods: A prospective study of adult CRS patients undergoing FSS (Draf 2 or Draf 3 procedures) was conducted at a tertiary care center. Primary outcomes included brief smell identification test (BSIT) and sinonasal outcome test‐22 (SNOT‐22), which were assessed during preoperative evaluation, 6 to 9 weeks postoperatively, and 12 to 24 weeks postoperatively. Normosmia was defined as BSIT ≥9. Statistical significance was determined using the Wilcoxon signed‐rank test with α  = .05. Results: Thirty‐eight patients followed up 12 to 24 weeks after FSS. The differences between baseline and long‐term outcomes for BSIT (6.11 vs. 8.24, P  = .00034) and SNOT‐22 (55.49 vs. 24.32, P  < .00001) scores were found to be statistically significant. Although both subgroups had clinically significant olfactory improvements, only the Draf 2 cohort experienced a statistically significant improvement in olfaction at long‐term follow‐up. There was no statistically significant change in data from 6 to 9 weeks to 12 to 24 weeks postoperatively. Conclusions: Patients undergoing total ethmoidectomy with FS demonstrated statistically significant increases in olfaction and QOL at long‐term postoperative follow‐up. This study demonstrated that FS does not negatively impact the olfactory improvement seen in sinus surgery. The lack of statistically significant changes in these olfactory metrics from short to long‐term follow‐up suggests that there is no additional negative effect of FSS in the long term. Level of Evidence: 3 Laryngoscope, 131:2173–2178, 2021